Lexical priming in spoken english usage - Pace-Sigge, Michael; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This book shows that over forty years of psychological laboratory-based research support the claims of the Lexical Priming Theory. It examines how Lexical Priming applies to the use of spoken English as the book provides evidence that Lexical Priming is found in everyday spoken conversations.
Keywords: Linguistics; Applied linguistics; Philology; Sociolinguistics; Lexicology; Linguistics; Sociolinguistics; Applied Linguistics; Language and Literature; Lexicology/Vocabulary.